Collaborative Strategy in Utilizing Restaurant Leftover Food for Vulnerable Communities in Depok City - Sikumbang, Idris Hadi (UI Scholars Hub, 2023)
Background: The largest waste component every year is waste originating from the wasteful culture and lifestyle of some city residents which has an impact on the generation of waste originating from waste/leftover food. Aims: This research aims to determine the city community's strategy for utilizing leftover food suitable for consumption produced by restaurants to be used to fulfill food needs for vulnerable communities in Depok City. Methods: This research was conducted using a mixed research method, explanation design method. The quantitative method consists of distributing questionnaires and observing secondary data, while the qualitative method consists of field observations and interviews. Results: The results of this research show that the people of Depok City really support efforts to utilize leftover food suitable for consumption from restaurants to fulfill the basic food needs of vulnerable residents. The desired strategy for managing leftover food suitable for consumption is through the formation of an official organization in collaboration with the local government and the private sector or the community which will develop and supervise standard procedures, concepts and implementation actions starting from the preparation of the leftover food program suitable for consumption, distribution and post-implementation of the program. Conclusion: The existence of this systematic collaborative organization is a guarantee of the fulfillment of halal aspects, health or hygienic aspects and aspects of the availability of leftover food suitable for consumption for vulnerable urban communities who need it.